Control of physiologic glucose homeostasis via hypothalamic modulation of gluconeogenic substrate availability - Jiaao Su; Abdullah Hashsham; Nandan Kodur; Carla Burton; Amanda Mancuso; Anjan Singer; Jennifer Wloszek; Abigail J. Tomlinson; Warren T. Yacawych; Jonathan N. Flak; Kenneth T. Lewis; Lily R. Oles; et al. (Molecular Metabolism)
Objectives: The brain mobilizes glucose in emergency situations such as hypoglycemia as well as during day-to-day physiology such as fasting. While most hypothalamic neuronal populations that contribute to glucose mobilization also contribute to other aspects of metabolism, neurons in the ventromedial nucleus of the hypothalamus that express the cholecystokinin b receptor (VMHCckbr neurons) support glucose production during hypoglycemia without controlling energy homeostasis. However, their role in day-to-day glucose physiology and the mechanisms they engage to support glucose mobilization is unclear. Methods: We used continuous glucose monitoring in mice with chronically silenced VMHCckbr neurons to establish whether these neurons are required during day-to-day glucose homeostasis. Tetanus-toxin based chronic silencing and acute optogenetic activation were followed by analysis of hepatic glucose metabolism and white adipose tissue lipolysis. Results: We found that VMHCckbr neurons support glucose homeostasis during short fasts and contribute to gluconeogenic substrate mobilization and lipolysis. VMHCckbr neurons mobilize glucose without depleting hepatic glycogen or increasing gluconeogenic gene expression, but instead mobilize glycerol in a β3-adrenergic receptor (β3-AR)-dependent manner. Restoring glycerol availability following VMHCckbr neuron silencing restores glucose. Finally, acute activation of VMHCckbr neurons mobilizes additional gluconeogenic substrates beyond glycerol. Conclusions: VMHCckbr neurons represent a distinct subset of glucose-mobilizing VMH neurons that support physiologic glucose homeostasis, likely through control of β3-AR-mediated gluconeogenic substrate mobilization and lipolysis. The presence of different glucose-mobilizing neuronal populations that engage distinct mechanisms in a context-dependent manner may provide the brain with flexibility to coordinate the appropriate glycemic response to different circumstances.